Do corporate and Sharia compliance governance affect enterprise risk management implementation? - Yang Elvi Adelina; Teddy Trilaksono; Rosdiana Rohi-Mone (University of Merdeka Malang, 2020)
The growth of Sharia banking assets in Indonesia greatly influenced by the scalability of Sharia banking businesses, which is supported by an increase in good corporate governance. The banking industry in general functions very closely with risk. This means that banks acutely need a risk-based management approach that is now being developed by the regulator with an integrated approach through Enterprise Risk Management (ERM). Other specific aspects of governance in Sharia banking include governance for compliance with Sharia aspects (Sharia compliance governance). The method used in this study is multiple regression analysis. We intended to examine the influence of general and Sharia governance mechanisms that exist in Indonesian Sharia banking with the level of ERM implementation. We indicated that the presence of the risk management committee, independent audit committee, and Sharia compliance audits positively and significantly affect ERM implementation. This study expected to be beneficial especially to provide input on governance policies for both banks and regulators.JEL Classification: G29, G30 How to Cite:Adelina, Y. E., Trilaksono, T., Rohi-Mone, R. (2020). Do corporate and Sharia compliance governance affect the enterprise risk management implementation?Jurnal Keuangan dan Perbankan, 24(1), 1-19.DOI: https://doi.org/10.26905/jkdp.v24i1.3768